Strategi Pengembangan Potensi Desa Wisata Sesaot Kecamatan Narmada Kabupaten Lombok Barat Melalui Pemberdayaan Masyarakat - Nurmayanti, Laila; Basuki, Prayitno; Ismiwati, Baiq (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to analyze the strategy for developing the potential of Sesaot Tourism Village through community empowerment and identify its inhibiting factors. The research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted using the SWOT analysis tool (Strengths, Weaknesses, Opportunities, Threats). The findings reveal that the community-based tourism development of Sesaot Tourism Village involves community participation in decision-making and provides both direct and indirect economic and social benefits. Supporting factors include abundant natural resources, diverse processed products, and the community's hospitality. However, inhibiting factors are the lack of professional workers and the low quality of human resources in tourism management. Recommended strategies include improving human resource quality through training, strengthening the concept of community-based tourism (CBT), and promoting sustainable tourism. This study highlights the importance of community empowerment in optimizing local tourism potential.